Neocolonialism or Balanced Partnership? Reframing Agricultural Relations Between the EU and Africa - Ioana Lungu (Policy Crossover Center: Vienna-Europe, 2017)
The media narratives with respect to EU external policies and their effects on developing countries generally paint a picture of unequal power dynamics and negative externalities, particularly with respect to international trade and land grabbing. In this paper, I use trade data to argue that reality is more nuanced and aim to provide a preliminary sketch of the institutional dynamics between the EU and Africa. I focus on agricultural relationships to highlight the interplay between historical path dependencies, colonialism, trade policy and domestic institutions on the EU and African side. While trade is often portrayed in an overly simplified manner as the main factor hindering agricultural development, African countries are often plagued by a long history of extractive institutions, both politically and economically, which lead to a vicious cycle of unequally distributed resources, exploitation, insecure human rights and a lack of incentives for innovation. This becomes apparent when examining phenomena such as land-grabbing, which often involve African elites partnering with foreign investors to conclude controversial deals. Overall, this paper aims to highlight the necessity of building institutional capacity particularly in countries with a long history of extractive institutional continuity, and to underline the importance of state centralisation for agricultural development, so that African partners can fully take advantage of the preferential trade regime with the EU and improve their position with respect to power dynamics.
Keywords: O19; O13; O17; O24; Q15; O20; 330; Agricultural Economics; Development; International Trade; Agricultural Policy; Governance; Foreign Assistance; Institution Building; Institutions; Least Developed Countries; Trade Liberalization